Visual methods and migration: methodological advantages using documentary in the field. Issue 4 (8th August 2022) - Crespi, Isabella; Scocco, Marta; Crescenti, Martina
Abstract : Visual methodology consists of recording, analysing, and communicating social life through photographs, films, and videos. This qualitative sociology branch considers the use of images as important techniques and methods in social research and identifies the primary role of visual experience in cognitive processes, through the visual data itself. In particular, the videos proposed in this contribution relocates the image of migrants' experiences in their most general context and allows documenting those social activities that require movement and continuity. Moreover, it allows analysing migrants' relationships and interactions over time, involving the visual image and sound. This contribution will discuss the importance and usefulness of visual methodology in two cases in which the visual documentary was used as a specific technique to investigate migration aspects. On the one hand, the documentary Who I am investigates the relational aspects of social inclusion, between migrant families and Italian people, in the specific context of afterschool services in Firenze. On the other hand, the documentary Italians in Belgium explores the migration phenomenon from a unique perspective, the ones of Italians living abroad. The analysis of the two types of research suggests how and why to use visual methodologies to improve and implement some practices during research in multicultural environments related to migration processes.